2009
DOI: 10.1073/pnas.0809406106
|View full text |Cite
|
Sign up to set email alerts
|

Heme uptake across the outer membrane as revealed by crystal structures of the receptor–hemophore complex

Abstract: Gram-negative bacteria use specific heme uptake systems, relying on outer membrane receptors and excreted heme-binding proteins (hemophores) to scavenge and actively transport heme. To unravel the unknown molecular details involved, we present 3 structures of the Serratia marcescens receptor HasR in complex with its hemophore HasA. The transfer of heme over a distance of 9 Å from its high-affinity site in HasA into a site of lower affinity in HasR is coupled with the exergonic complex formation of the 2 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
152
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 41 publications
5
152
1
3
Order By: Relevance
“…Spectroscopic and structural characterization of HasR of Serratia marcescens and ShuA of Shigella dysenteriae have confirmed heme to be coordinated through a His on the face of the N-terminal plug occluding the membrane spanning ␤-barrel, and a corresponding His on the extracellular FRAP/PNPNL loop ( Fig. 1) (23)(24)(25). Interestingly, the majority of heme receptors so far characterized, both hemophore-dependent and independent, have the characteristic bis-His coordination.…”
mentioning
confidence: 95%
“…Spectroscopic and structural characterization of HasR of Serratia marcescens and ShuA of Shigella dysenteriae have confirmed heme to be coordinated through a His on the face of the N-terminal plug occluding the membrane spanning ␤-barrel, and a corresponding His on the extracellular FRAP/PNPNL loop ( Fig. 1) (23)(24)(25). Interestingly, the majority of heme receptors so far characterized, both hemophore-dependent and independent, have the characteristic bis-His coordination.…”
mentioning
confidence: 95%
“…Over the past three decades, many aspects of this TonB-ExbB-ExbD-dependent transport system have been revealed. The crystal structures of several OM transporters and their complexes with TonB are now known (Ferguson et al, 1998(Ferguson et al, , 2002Buchanan et al, 1999;Ferguson and Deisenhofer, 2004;Pawelek et al, 2006;Shultis et al, 2006;Krieg et al, 2009), the signal transduction of OM transporters by interaction with TonB has been elucidated (Ferguson et al, 2007;Kim et al, 2007) and the rotational mechanism of TonB motion has been reported (Jordan et al, 2013). However, with regard to the substrates of the transport system, we are probably only seeing the 'tip of the iceberg' (Schauer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many virulence studies have taken advantage of the fact that TonB is universally required for iron and heme uptake in Gram-negative bacteria and they have targeted it directly to circumvent issues with overlapping iron acquisition systems (discussed above). TonB-dependent receptors are structurally conserved and share an amino acid consensus sequence termed the "TonB box," which interacts with TonB (42,43). Once the heme or iron has been transported across the outer membrane, a substrate-specific periplasmic binding protein ferries the substrate to an ATP-binding cassette (ABC) transport system that moves it into the cytosol (39) (Fig.…”
Section: Bacterial Iron and Heme Acquisition Systemsmentioning
confidence: 99%